The Influence of Information Order Effects and Trait Professional Skepticism on Auditors’ Belief Revisions A Theoretical and Empirical Analysis - Yankova, Kristina. (Auditing and Accounting Studies, 2015)
Kristina Yankova addresses the question of what role professional skepticism plays in the context of cognitive biases (the so-called information order effects) in auditor judgment. Professional skepticism is a fundamental concept in auditing. Despite its immense importance to audit practice and the voluminous literature on this issue, professional skepticism is a topic which still involves more questions than answers. The work provides important theoretical and empirical insights into the behavioral implications of professional skepticism in auditing.  Contents Belief Revision and Information Order Effects Professional Skepticism Empirical Analysis  Target Groups Researchers and students in the fields of accounting and auditing Practitioners in these areas  The Author Dr. Kristina Yankova completed her doctoral studies under the guidance of Prof. Dr. Annette Köhler at the Chair of Accounting and Auditing at the Mercator School of Management, University of Duisburg-Essen.